Urgensi Perlindungan Hukum terhadap Konservasi Ikan Air Tawar Endemik di Indonesia - Nayla Hasana; Novenia Cecilia Nadeak (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The Indonesian government has been actively combating illegal fishing practices at sea because they harm the country and reduce fish populations. However, attention to freshwater fisheries, especially endemic fish, is still limited. In fact, endemic fish play an important role in aquatic ecosystems and local culture. Fish resource conservation aims to protect, preserve, and utilize fish and their ecosystems and genetic diversity so that their existence and availability remain sustainable. The diversity of freshwater fish in Indonesia faces serious threats from human activities. The main factor is the introduction of new species that grow uncontrollably, becoming pests and harming ecosystems and communities. In addition, overfishing and declining habitat quality further exacerbate the situation. These threats pose a risk of extinction for endemic fish. Therefore, conservation efforts need to be strengthened to maintain ecosystem balance and support the livelihoods of communities that depend on fish farming. Legal protection is an important aspect in addressing this issue. Law No. 31 of 2004 concerning Fisheries and Law No. 5 of 1990 concerning Conservation of Living Natural Resources and Ecosystems have provided a legal basis for fish resource management. However, their implementation and enforcement remain weak. This study uses a normative juridical approach with secondary legal materials, emphasizing the importance of improving the legal framework and more effective governance. Measurable, transparent, and sustainable conservation measures are needed to ensure the optimal utilization of fish resources. Thus, the sustainability of freshwater ecosystems and the welfare of communities that depend on endemic fish can be guaranteed.